2019
DOI: 10.3390/plants8030054
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Nine Pyrrolizidine Alkaloids in Senecio vulgaris L. Depending on Developmental Stage and Season

Abstract: The contamination of phytopharmaceuticals and herbal teas with toxic plants is an increasing problem. Senecio vulgaris L. is a particularly noxious weed in agricultural and horticultural crops due to its content of toxic pyrrolizidine alkaloids (PAs). Since some of these compounds are carcinogenic, the distribution of this plant should be monitored. The amount of PAs in S. vulgaris is affected by various factors. Therefore, we investigated the occurrence of PAs depending on the developmental stage and season. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 62 publications
(103 reference statements)
0
23
0
1
Order By: Relevance
“…Recently, the PA/PANO sum contents in Senecio vulgaris L. were determined and shown to range from 0.16% to 0.49% related to dry matter, depending on the developmental stage and season [24]. Compared to the highest content of PA/PANO analytes detected in oregano in our current study (24.6 mg/kg), that indeed mainly originated from Ht-type compounds, this would correspond to a proportion of 1.54% to 0.50% of pure PA/PANO plants in this oregano sample.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the PA/PANO sum contents in Senecio vulgaris L. were determined and shown to range from 0.16% to 0.49% related to dry matter, depending on the developmental stage and season [24]. Compared to the highest content of PA/PANO analytes detected in oregano in our current study (24.6 mg/kg), that indeed mainly originated from Ht-type compounds, this would correspond to a proportion of 1.54% to 0.50% of pure PA/PANO plants in this oregano sample.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding further uncertainties and influences, plant-specific and seasonal fluctuations in the PA/PANO levels must also be taken into account. A recent study of Flade et al showed clear differences in the PA and PANO contents depending on the season and stage of the development of the plant (S. vulgaris) [58]. S. aquaticus as well as S. inaequidens also showed high seasonal fluctuations in PA/PANO occurrences [59,60].…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, terpenoid biosynthesis is known to be under strong genetic control [82,83], although some degrees of phenotypic plasticity can be observed in terpene production as a response to abiotic factors [84] and, in our case, to soil fertilization. Abiotic factor-induced changes in the concentrations of individual secondary metabolites of the same compound class were found for pyrrolizidine alkaloids in Senecio (Asteraceae) [85], for phenylpropanoid compounds in tobacco [86] and for phenolics in Trifolium pratense [87].…”
Section: Discussionmentioning
confidence: 95%